Challenges in Treating Secondary Syphilis Osteitis in an Immunocompromised Patient with a Penicillin Allergy: Case Report and Review of the Literature. (29th May 2016) - Ali, Robert; Perez-Downes, Julio; Baidoun, Firas; Al Turk, Bashar; Isache, Carmen; Mohan, Girish; Perniciaro, Charles
Abstract : Syphilis is a sexually transmitted infection that remains fairly commonplace. The introduction of penicillin aided in curbing the incidence of disease; however, with the advent of the human immunodeficiency virus (HIV), syphilis is now on a resurgence with sometimes curious presentations. We present a case of a 36-year-old Caucasian gentleman with untreated HIV who complained of a skin eruption and joint pains for 6 weeks, prompting the diagnosis of secondary syphilis osteitis. Skin lesions were reminiscent of "malignant" syphilis. CD4 count was 57 cells/ μ L. RPR was elevated with 1 : 64 titer and positive confirmatory TP-PA. Radiography of the limbs revealed polyostotic cortical irregularities corroborated on bone scintigraphy. The patient had an unknown penicillin allergy and was unwilling to conduct a trial of penicillin-based therapy. He was subsequently treated with doxycycline 100 mg twice daily for 6 weeks and commenced antiretroviral therapy, noting dramatic improvement in both the skin lesions and joint pains. Unfortunately, he defaulted on follow-up, precluding serial RPR and bone imaging. Penicillin allergies have proven to be quite a conundrum in such patients, without much recourse for alternative therapy. Doxycycline with/without azithromycin is other options worth considering.